Perspectives of youths on cultural ecosystem services provided by Tun Mustapha Park, Malaysia through a participatory approach. Issue 1 (2nd January 2023) - Mohd Noor, Mohd Iqbal; N. Alagappar, Ponmalar; Then, Amy Yee-Hui; Justine, Eva Vivian; Lim, Voon-Ching; Goh, Hong Ching
Abstract: Successful buy-in and support for management of Marine Protected Areas (MPA) should acknowledge the existing cultural ecosystem services and their connections to the well-being of local communities to gain positive perceptions. It is necessary to engage local stakeholders, especially among the youths, to explore governance complexities of MPAs and how to better understand cultural ecosystem services. Thus, this qualitative study investigated the perceptions of youths on cultural ecosystem services using a visual method, namely photovoice, as part of the participatory research in a newly established MPA of Tun Mustapha Park, Sabah. Three themes were identified in the process, namely social, economic, and environment. The engagement demonstrated the value of using the participatory approach, which yielded important insights of youths as a part of the community, which included the need for additional livelihood means post-establishment of MPA and issues of degradation of the marine environment. This paper contributed to the MPA governance literature specifically on the empirical youth perception which has been underrepresented as well as the employment of visual participatory methods to encourage better expression among the youths towards their living environment.